2020
DOI: 10.3390/nu12051490
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Motivations for Food Choices and Consumption of Food Groups: A Prospective Cross-Sectional Survey in Manufacturing Workers in Brazil

Abstract: Motivations for food choices may determine consumption, and understanding that relationship may help direct strategies for formulating diets. This study aimed to identify associations between motivations for food choices and consumption of food groups. An observational cross-sectional survey was conducted in 921 manufacturing workers from 33 companies in Brazil, based on a stratified two-stage probability sample. Motivations for food choices were assessed with the Food Choice Questionnaire, and intake of food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
4
12
0
3
Order By: Relevance
“…Similar determinants have been declared by adult populations in different studies; for example, manufacturing workers in Brazil indicated sensory appeal and price as the most important determinants [43]; relatives of secondary and high school students in Spain indicated sensory appeal, price, and weight control [44]; adults from Western Balkan countries indicated sensory appeal, convenience, health, and natural content [45]; individuals from Belgium, Hungary, and Romania indicated sensory appeal, health, convenience, and price; and individuals from the Philippines indicated health, price, mood, and sensory appeal [27]. In the comprehensive study of Markovina conducted in 9 European countries, price was found to be the most important determinant of food choices in Spain, Greece, Ireland, Portugal, and the Netherlands, sensory appeal in Norway, Germany, and the United Kingdom, and natural content in Poland, while familiarity and ethical concern were consistently ranked as the least important by the populations of all the studied countries [46].…”
Section: Discussionsupporting
confidence: 78%
“…Similar determinants have been declared by adult populations in different studies; for example, manufacturing workers in Brazil indicated sensory appeal and price as the most important determinants [43]; relatives of secondary and high school students in Spain indicated sensory appeal, price, and weight control [44]; adults from Western Balkan countries indicated sensory appeal, convenience, health, and natural content [45]; individuals from Belgium, Hungary, and Romania indicated sensory appeal, health, convenience, and price; and individuals from the Philippines indicated health, price, mood, and sensory appeal [27]. In the comprehensive study of Markovina conducted in 9 European countries, price was found to be the most important determinant of food choices in Spain, Greece, Ireland, Portugal, and the Netherlands, sensory appeal in Norway, Germany, and the United Kingdom, and natural content in Poland, while familiarity and ethical concern were consistently ranked as the least important by the populations of all the studied countries [46].…”
Section: Discussionsupporting
confidence: 78%
“…Traditional food and fast food have different nutrients and contribute differently to consumer diets. Given the importance of understanding consumer motivations for eating behavior and food choice [13], the findings of this study provide implications for academic researchers, business practitioners, and policymakers in several manners.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional food refers to foods and dishes that are passed through generations, whereas fast food is a type of mass-produced food designed for commercial resale and with a strong priority placed on speed of service versus other relevant factors involved in culinary science [2,5,11]. Notably, fast food consumption has been considered as an unfavorable eating behavior, contributing to overweight and obesity [3,12,13]. By contrast, traditional food is not necessarily healthy but considered as better than fast food in the eyes of consumers [2].…”
Section: Introductionmentioning
confidence: 99%
“…O homem, enquanto ser social, é influenciado pelos mais diversos fatores que igualmente impactam nas escolhas alimentares (BARUFALDI et al, 2016;MAIA et al, 2018). As preferências do indivíduo são constituídas com base, principalmente, nos fatores socioeconômicos, culturais, cognitivos, hábitos familiares, crenças aprendidas, assim como nos mecanismos fisiológicos e genéticos (LENG et al, 2017;SOUZA et al, 2020). Apesar de parecer simples, as escolhas alimentares são processos complexos determinados por diferentes razões e suas interações (KÖSTER, 2007).…”
Section: Fatores Determinantes Das Escolhas Alimentaresunclassified
“…Em publicação com trabalhadores brasileiros, Souza et al (2020) observaram que os fatores mais influentes nas escolhas dos alimentos foram o apelo sensorial, preço e conveniência e os que causam menores impactos foram a preocupação com as questões éticas, humor e conteúdo natural dos alimentos.…”
Section: Fatores Determinantes Das Escolhas Alimentaresunclassified